PHYSICAL ACTIVITY IN PSYCHIATRY: MECHANISMS AND EFFICACY IN THE INTEGRATED TREATMENT OF DEPRESSION - Agnieszka Zaleszczyk; Katarzyna Oświeczyńska; Agnieszka Kasprzak; Patrycja Jędrzejewska-Rzezak (International Journal of Innovative Technologies in Social Science, 2025)
Depression is a serious mental disorder that manifests itself primarily as sadness, lack of energy, and reduced activity, which often hinders normal functioning. People who struggle with depression often feel overwhelmed by their lives. This mental disorder can take a variety of forms, ranging from temporary mood swings in everyday life to a serious clinical condition with significant symptoms and additional signs that clearly differ from what is considered normal. Treatment includes both pharmacotherapy and psychological therapy. Evidence for the effectiveness of this approach is solid and supported by numerous studies. However, it is worth noting that each patient is unique in terms of mental health and should be treated individually. Therefore, alternative methods may be considered and their effectiveness in the prevention and treatment of mental illnesses of civilization, especially in the context of depression, may be tested. An analysis of the available literature indicates that high levels of physical activity and regular exercise have a protective effect against depression. In combination with other forms of treatment, exercise and physical activity can contribute to a faster improvement in patients’ health. This publication is a review and focuses on standardizing the definition of depression in relation to its significance in combination therapy. Physiological mechanisms that show how physical activity affects well-being were examined. The work is based on scientific research in the context of clinical trials. Practical tips on physical activity in cases of depression are also included, and obstacles and limitations are discussed.